The 'arms dynamic' in South-East Asia during the second Cold War - Rolls, Mark G. (Ashgate, 2002)
This text analyzes the status of the nations of Southeast Asia with regard to technological progression in arms and traces the anarchic flow of weapons technology over the period following the demise of the Soviet system in the early-1990s.